2007
DOI: 10.1002/pssc.200675230
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of pristine and annealed nanocrystalline TiO2 thin films by X‐ray diffraction and Raman spectroscopy

Abstract: Nanocrystalline anatase TiO 2 films were prepared from colloidal suspensions using particles with a nominal size of 12 nm. Their structure was examined by Raman spectroscopy and X-ray diffraction (XRD). The as-prepared specimens exhibit exclusively features due to the anatase phase of TiO 2 (e.g., the E g , B 1g and A 1g vibration modes in Raman spectroscopy and the characteristic diffraction peaks in XRD). Isochronal annealing of the films in air at temperatures of up to 1320 K effected clear structural chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…7 displays the FWHM of the E g(1) Raman phonon versus R. The FWHM decreases as R also decreases (observe the direction of arrow), like cubic CeO 2 nanoparticles where FWHM diminishes as R decreases [26]. But, actually, this result is contrary to the tendency expected in most peak line-width versus R data [8,[27][28][29], where FWHM increases when R decreases. Besides, the inset of Fig.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…7 displays the FWHM of the E g(1) Raman phonon versus R. The FWHM decreases as R also decreases (observe the direction of arrow), like cubic CeO 2 nanoparticles where FWHM diminishes as R decreases [26]. But, actually, this result is contrary to the tendency expected in most peak line-width versus R data [8,[27][28][29], where FWHM increases when R decreases. Besides, the inset of Fig.…”
Section: Resultscontrasting
confidence: 72%
“…The Raman spectrometry technique has been a useful and important tool and there have been a variety of publications that interpret of different manners the behavior of the vibrational modes of a Titania matrix as the radius of nanoparticles changes due to the incorporation of different types of ions. Among these interpretations are phonon confinement, non-stoichiometry or internal/stress surface tension effects [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Half width of the E g peak vs. crystallite size as deduced from XRD, including results from the literature. 4,18,27,28,35,36 thickness obtained from the simulation of the transmittance data are close to that obtained by profilometry (see Fig. 7).…”
Section: B Optical Characterizationsupporting
confidence: 78%
“…Orendorz et al 36 also observed that the prominent E g 144 cm À1 mode of their nanocrystalline anatase TiO 2 films is blueÀshifted and the FWHM varies as a power of the inverse of crystallite size. These films were prepared from colloidal suspensions using particles of 12 nm size and their crystallite sizes were varied from $13 to $125 nm upon annealing at higher temperatures without any phase transformation.…”
Section: Resultsmentioning
confidence: 91%
“…The structural properties of such films are subject to several publications [19] [20] [21] [22] [23]. The DTPT was prepared following the synthesis as described in [9] and [10].…”
Section: Density Functional Theorymentioning
confidence: 99%